Examining the Challenges of HIV Positive People With Disabilities in Accessing Medical Services in Rukungiri District: A Case Study of Nyakishenyi Sub-County - Atuheire, Fortunate (Kabale University, 2023)
The study examined the challenges of HIV-positive people with disabilities in accessing medical services in Rukungiri district: a case of Nyakishenyi Sub County. The objectives of the study were; to examine the HIV prevalence rate among persons with disabilities 111 Nyakishenyi Sub County Rukungiri District, to establish the factors that hinder people with disabilities in accessing medical services in Nyakishenyi Sub County Rukungiri District, and to examine the solutions to how persons living with disabilities can access medical services. A descriptive research design was used and data was collected using questionnaires and interviews. The study findings on the prevalence rate among persons with disabilities, the prevalence rate of females was high compared to the least number of respondents who were males. The study findings on factors that hinder people with disabilities in accessing medical services were; discrimination due to their disabilities, poor assumptions that persons with disabilities are not at risk of contracting HIV and therefore do not require access to HIV prevention, poverty among the people with disabilities, inaccessibility of health services and exclusion of people with disabilities from sexuality education. The study findings on the preventative strategies of HIV among persons living with disabilities were; reduction of stigma and discrimination from persons with disabilities, establishing some programs that can generate income for persons with disabilities, ensuring provision of sexuality education to persons with disabilities, and avoiding poor assumptions that persons with disabilities are not at risk of contracting HIV and therefore do not require access to HIV education. The study recommended that there is a need to adopt appropriate and disability-sensitive channels of communication to disseminate HIV/AIDS messages/information to the community of people with disabilities, there is a need to print HIV/AIDS posters with people with disabilities on them to attract the attention of the public and stir them into positive action and intervention and there should be promotion of adult literacy programs for people with disabilities to enable them to read, write and interpret disseminated HIV/AIDS messages.